The Effects of Vitamin D on Metabolic Profiles in Women with Polycystic Ovary Syndrome: A Systematic Review - Williams, Ashley; Babu, Jeganathan Ramesh; Wadsworth, Danielle D.; Burnett, Donna; Geetha, Thangiah (Hormone and Metabolic Research, 2020)
This systematic review aims to evaluate all epidemiological evidence in the literature linking the effect of vitamin D supplementation to metabolic and hormonal functions in women with polycystic ovary syndrome. The literature search was performed with two databases, namely Medline/PubMed and Web of Science, until 20 May 2019 for both observational and experimental studies concerning relationships between vitamin D and polycystic ovary syndrome. A total of ten studies with randomized, double-blinded, and placebo-controlled trial design from 2008 to 2019 were selected for this review. The inclusion criteria were women 18–45 years of age with polycystic ovary syndrome and comparing the metabolic or endocrine parameters between placebo and vitamin D supplementation groups. A total of ten studies were selected for this review. We found that vitamin D supplementation had a significant effect on insulin metabolism, total serum testosterone, hirsutism, C-reactive protein, and total antioxidant capacity in women with polycystic ovary syndrome. Evidence from available randomized controlled trials suggests that patients with polycystic ovary syndrome should take vitamin D supplementation for the beneficial effect of metabolic profiles. However, future research is needed regarding the beneficial effects in women who are non-obese with polycystic ovary syndrome, as well as more studies with larger sample sizes.
Keywords: polycystic ovary syndrome; vitamin D; systematic review; randomized controlled trials